(untitled) (American Journal of Arts and Human Science, 2025)
Over the past few years, the UAE has been a major player in Somalia by gaining port contracts, forming and training special forces, building alliances with the Federal Government, and also maintaining friendly ties with Somaliland, a self-declared independent province but lacking international recognition. These actions have fueled domestic unrest and harmed Somalia’s unity, sovereignty, and democratic processes. Thus, this paper examines Somali-UAE bilateral relations from 2000 to 2022. The study sought to ascertain Somalia’s strategic position within UAE foreign policy, identify the factors that bolster Somalia-UAE relations, and explore potential avenues for the expansion of these linkages. The study utilized a qualitative technique grounded in descriptive and historical research designs. Secondary sources were examined and assessed. The study indicated that the United Arab Emirates established a military facility in Somalia for political and security purposes. According to the research, Somalia needs a pragmatic and assertive foreign policy strategy to promote its national interests. The research uncovered that UAE trade indexes are increasing, while Somalia’s is declining. However, political stability and security reform could attract international investors. Diplomatic relations between Somalia and the UAE are improving with multilateral security agreements and renewed security sectors. Finally, the study recommends that the UAE leadership respect Somalia’s sovereignty and territorial unity, safeguarding brotherly relations. The paper also suggests that the Somali government should elucidate its foreign policy, goals, and relationships with Arab League and OIC countries—the research further advocates for enhancing trade, security, and economic collaboration with the UAE.